2012
DOI: 10.1007/s12098-012-0952-0
|View full text |Cite
|
Sign up to set email alerts
|

Current Challenges and Future Prospects of Neonatal Care in India

Abstract: Maternal and neonatal health is the current focus of central and state governments as well as various funding organizations. There is a lot happening in terms of expansion of secondary healthcare facilities and training of the healthcare personnel. This offers an exciting opportunity like never before, for those interested in the welfare of the newborns. Although infant and neonatal mortality rates in our country have been falling progressively, the pace has been much slower than expected, especially for neona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…For providing these services, three levels of newborn care have been defined in literature. 2, 9, 10, 11 The complexity of management of sick newborns has been used to define the level of care that can be provided at different healthcare facilities. The services provided at each level is a product of infrastructure, availability of skilled manpower and referral capacity of the institution.…”
Section: Structure Of Delivery Of Fbncmentioning
confidence: 99%
See 1 more Smart Citation
“…For providing these services, three levels of newborn care have been defined in literature. 2, 9, 10, 11 The complexity of management of sick newborns has been used to define the level of care that can be provided at different healthcare facilities. The services provided at each level is a product of infrastructure, availability of skilled manpower and referral capacity of the institution.…”
Section: Structure Of Delivery Of Fbncmentioning
confidence: 99%
“…10, 11 Assuming that the private sector may provide some proportion of these beds, the number of existing beds in the public sector SNCUs is still short of the estimates. Ultimately, each district would require additional SNCUs to cater to sick newborns.…”
Section: Implementation Challenges Of Facility-based Care and Opportumentioning
confidence: 99%
“…The WHO (2010) reported nations with the most profound nursing shortages have the highest rates of infant mortality and the poorest health outcomes. According to recent global statistics, India has the most neonatal deaths per year in the world (Bhakoo and Kumar 2013). More studies are needed to identify the perceived rewards of nursing by students and nurses from a variety of religious backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between socio-economic determinants and IMR/NMR is not linear as shown by Bhakoo et al, Sharma et al]. 17,20 Data from Roy et al, showed predominance of socio-economic status class 4 and 5. 14 In view of rural setting kuccha housing, overcrowding, poor sanitation, lack of accessibility to safe water supply was major hurdles in almost half the families.…”
Section: Demographic Characteristicsmentioning
confidence: 95%